Solitude im Museum. - Musée d'Art moderne de Saint-Etienne, Saint-Etienne; Staatsgalerie Stuttgart; Asthoff, Jens; Baumann, Daniel; Beauffet, Jacques; Blase, Christoph; Chabrillat, François Joseph; Dancer, Martine; De Cecco, Emanuela; Demir, Anaïd; Fernández, Nicolas; Gauss, Ulrike; et al. (Stuttgart : Akademie Schloss Solitude, 2000)
Birchler, Alexander ; Chabrillat, François Joseph ; Comte, Serge ; Fernández, Nicolas ; Gruppo A 12 ; Hubbard, Teresa ; Jürss, Ute Friederike ; Kaufman, Betsy ; Lämmli, Dominique ; Lamunière, Simon ; Meierhofer, Christine ; Pepperstein, Pavel ; Pocock, Philip ; Sander, Karin ; Shrigley, Gordon ; Siem, Wiebke ; Waddell, Stephen
biog., ind. tent., gr. tent., bibliog. per kunstenaar
Text English-German-French
Solitude im Museum, Staatsgalerie Stuttgart, 30.09. - 12.11.2000 ; Musée d'Art Moderne de Saint-Etienne, 14.12.2000 - 26.03.2001
kunstcatalogus